Prognostic impact of recurrences in patients with electrical storm. (4th March 2019) - Müller, Julian; Behnes, Michael; Ellguth, Dominik; Schupp, Tobias; Mashayekhi, Kambis; Borggrefe, Martin; Akin, Ibrahim
Abstract: Objectives . The study sought to assess the prognostic impact of recurrences of electrical storm (ES-R) on mortality, rehospitalization and major adverse cardiac events (MACE). Background . Data on the prognostic impact of ES-R is rare. Methods . All consecutive ES patients with an implantable cardioverter defibrillator (ICD) were included retrospectively from 2002 to 2016. Patients with ES-R were compared to patients without ES-R. The primary endpoint was all-cause mortality, secondary endpoints were in-hospital mortality, rehospitalization and MACE. Results . A total of 87 consecutive ES patients with an ICD were included, of which 26% presented with ES-R at 2.5 years of follow-up. ES-R patients revealed lower LVEF compared to non-ES-R patients (91% vs. 61%; p  = .081). There was a numerically higher rate of the primary endpoint of all-cause mortality at 2.5 years (50% vs. 32%; log-rank p  = .137). Furthermore, ES-R was associated with increasing rates of rehospitalization (64% vs. 37%; p  = .031; HR 1.985; 95% CI 1.025–3.845; log-rank p  = .042), especially of acute heart failure (32% vs. 12%; p  = .001; HR 3.262; 95% CI 1.180–9.023; log rank p  = .023). MACE were higher in ES-R patients (55% vs. 35%; p  = .113; log rank p  = .141). ES patients with LVEF ≤35% were 12.4 times more likely to develop ES-R (HR 12.417; 95% CI 1.329–115.997; p  = .027). Conclusion . At long-term follow-up of 2.5 years, ES-R was associated with numerically higher rates of long-term all-cause mortality and significantly higher rates of rehospitalization due to acute heart failure. LVEF ≤35% was associated with increased risk of ES-R. Condensed Abstract This study examined retrospectively the impact of recurrences of electrical storm (ES-R) on survival in 87 patients. ES-R was associated with numerically higher long-term all-cause mortality, whereas significantly higher rates of rehospitalization, respectively of acute heart failure were observed. Highlights: ES-R is associated with numerically higher rates of all-cause mortality at long-term follow-up. ES-R is associated with significantly higher rates of rehospitalization and numerically higher rates of MACE at long-term follow-up, mainly due to acute heart failure. Patients with LVEF ≤35% were 12.4 times more likely to develop ES-R.